Electrically tunable two-dimensional heterojunctions for miniaturized near-infrared spectrometers - Deng, Wenjie (2023)
Miniaturized spectrometers are of considerable interest for their portability. Most designs to date employ a photodetector array with distinct spectral responses or require elaborated integration of micro & nano optic modules, typically with a centimeter-scale footprint. Here, we report a design of a micron-sized near-infrared ultra-miniaturized spectrometer based on two-dimensional van der Waals heterostructure (2D-vdWH). By introducing heavy metal atoms with delocalized electronic orbitals between 2D-vdWHs, we greatly enhance the interlayer coupling and realize electrically tunable infrared photoresponse (1.15 to 1.47 μm). Combining the gate-tunable photoresponse and regression algorithm, we achieve spectral reconstruction and spectral imaging in a device with an active footprint < 10 μm. Considering the ultra-small footprint and simple fabrication process, the 2D-vdWHs with designable bandgap energy and enhanced photoresponse offer an attractive solution for on-chip infrared spectroscopy.